Peran Politik Perempuan dan Hukum Di Indonesia - Isnawati Isnawati (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2016)
In Indonesia since the reforms, political participation of women, especially women's representation in decision-making becomes an important agenda of government and the legislature. affirmation and strengthening policies continue to be pursued. In the representation of women in decision-making, of course we have followed with a mindset, as well as the ability of the competent. But the fact is, we are very concerned about the condition of women's political participation tends to be a bit of strength. Social and cultural processes, are more likely to exclude women, is considered negative for the condition and behavior. Therefore, efforts need to change the mindset (mind-set) of society on women's lives.